2022
DOI: 10.1186/s13578-022-00828-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism and storage in neuroglia: role in brain development and neurodegenerative diseases

Abstract: The importance of neuroglia in maintaining normal brain function under physiological and pathological conditions has been supported by growing evidence in recent years. The most important issues regarding glial metabolism and function include the cooperation between glial populations and neurons, morphological and functional changes in pathological states, and the role in the onset and progression of neurodegenerative diseases. Although lipid accumulation and further lipid droplet production in neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 137 publications
0
34
0
Order By: Relevance
“…Integrated analysis was performed to understand the network of relationships between altered lipidomics and transcriptomics. Dynamic changes in lipid metabolism within neurons and glial cells resulting in lipid accumulation and lipid droplet formation are present in brain models of various neurodegenerative diseases ( Yang et al, 2022 ), and myelin sheath is essential for the normal function of peripheral nerves. The results suggested that the downregulation of CYP1A2 expression may be responsible for PC accumulation, as shown in Figure 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrated analysis was performed to understand the network of relationships between altered lipidomics and transcriptomics. Dynamic changes in lipid metabolism within neurons and glial cells resulting in lipid accumulation and lipid droplet formation are present in brain models of various neurodegenerative diseases ( Yang et al, 2022 ), and myelin sheath is essential for the normal function of peripheral nerves. The results suggested that the downregulation of CYP1A2 expression may be responsible for PC accumulation, as shown in Figure 4 .…”
Section: Discussionmentioning
confidence: 99%
“…These thoughts are consistent with our co-culture experiments in which low density astrocytes (10%), in comparison to physiological numbers of 1.5 astrocyte-to-neurons in the cerebral cortex [ 29 ], were enough to significantly protect neurons from THC-induced damage. We firstly attribute the protective effect on the physical presence of astrocytes, providing passive protection by forming a larger lipid bilayer pool for THC to interact with [ 56 ], in addition to its possible capture into de novo created astrocytic lipid droplets in response to stressors [ 57 , 58 ]. Second, even though astrocyte conditioned medium had no effect in preventing THC-induced damage, the close physical contact of neurons with astrocytes would allow for immediate local glutamate scavenging, as well as the release of high concentrations of ATP [ 59 ] and antioxidants [ 55 ], both independent of vesicular release [ 60 , 61 ], directly onto the neuron, otherwise diluted in cell culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…31 The LD-rich glial cells are less sensitive to harmful reactive oxygen species (ROS) activity than neurons, so they are considered the main site of FA storage and lipid metabolism in the brain. 32 Neuronal FAs that are not been used during the electron transport chain (ETC)-mediated synthesis of adenosine triphosphate (ATP) are transported to glial cells by apolipoproteins. As the accumulation of FAs is toxic to neuronal cells, FAs must be stored as TAGs in LDs.…”
Section: Alterations In Lipid Levels and Their Distribution In Drosop...mentioning
confidence: 99%